Penggunaan Aplikasi Quiziz dan Relevansinya dengan Rekognisi Pembelajaran Daring Matematika di MAN 1 Model Bojonegoro - Agustinayanti (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2021)
Abstract: This study reveals online Mathematics learning in the MAN 1 Bojonegoro Model on the pandemic table. Data with descriptive quantitative retrieval to comprehensively describe the bold pinking problem of how it is analyzed to optimize through the Applique Quiz. Some of the learning problems of courage that were found were: 1) Weaknesses of teachers and rumpy participants in utilizing information technology in courageous learning, 2) Teachers and schools/madrasahs are limited by the distance in controlling the bell for development of play abilities, hash control the pink learning platform, 4) School / Madrasah has not controlled the platform has a unique platform as a medium for pink evaluation of lessons. The presence of Quiz applique as an efficient solution to solve all problems that are evaluative exercises. In addition to free access and free users, Quiz also has exclusive features in doing questions and has fish bait for teachers that can be used as a reference for the development of students' abilities. Interested meandering participants, interactive from the fun. Abstrak: Penelitian ini mengungkap rekognisi pembelajaran Matematika secara online di MAN 1 Model Bojonegoro pada masa pandemi ini. Data dianalisis dengan pendekatan kualitatif deskriptif untuk menggambarkan secara komprehensif mengenai problem pembelajaran daring dan cara untuk mengoptimalkan melalui aplikasi Quiziz. Beberapa probelematika pembelajaran daring yang ditemukan adalah: 1) Kelemahan guru dan peserta didik memanfaatkan tekhnologi informasi pada pembelajaran daring, 2) Guru dan sekolah/Madrasah terbatasi oleh jarak dalam mengontrol perkembangan kemampuan pelajaran Matematika, 3) belum memiliki platform model latihan soal untuk mengevaluasi hasil pembelajaran, 4) Sekolah/Madrasah belum memiliki platform khusus sebagai mediai pembelajaran dan evaluasi. Kehadiran aplikasi Quiziz sebagai solusi efektif dan efisien untuk menyelesaikan segala problem yang bersifat latihan evaluatif. Selain free acces dan free user, Quiziz juga memiliki fitur yang lengkap dalam mengerjakan soal, dan memiliki umpan balik kepada guru yang dapat dijadikan rujukan pengetahuan perkembangan kemampuan peserta didik. Peserta didik merasa tertarik, menyenangkan dan interaktif.   DOI: https://doi.org/10.33399/edukasia.v2i1.38